A brain glioma gene delivery strategy by angiopep-2 and TAT-modified magnetic lipid-polymer hybrid nanoparticles. Issue 68 (13th November 2020) - Qiao, Lanxin; Qin, Yu; Wang, Yaxin; Liang, Yi; Zhu, Dunwan; Xiong, Wei; Li, Lu; Bao, Di; Zhang, Linhua; Jin, Xu
Abstract : The gene delivery system can penetrate the BBB model efficiently and transfect C6 glioma cells effectively in magnetic field. Abstract : Owing to the existence of the blood–brain barrier (BBB), most treatments cannot achieve significant effects on gliomas. In this study, synergistic multitarget Ang-TAT-Fe3 O4 -pDNA-(ss)373 lipid-polymer hybrid nanoparticles (LPNPs) were designed to penetrate the BBB and deliver therapeutic genes to glioma cells. The basic material of the nanoparticles was PCL3750 -ss-PEG7500 -ss-PCL3750, and is called (ss)373 herein. (ss)373 NPs, Fe3 O4 magnetic nanoparticles (MNPs), DOTAP, and DSPE-PEG-MAL formed the basic structure of LPNPs by self-assembly. The Fe3 O4 MNPs were wrapped in (ss)373 NPs to implement magnetic targeting. Then, the Angiopep-2 peptide (Ang) and transactivator of transcription (TAT) were coupled with DSPE-PEG-MAL. Both can enhance BBB penetration and tumor targeting. Finally, the pDNA was compressed on DOTAP to form the complete gene delivery system. The results indicated that the Ang-TAT-Fe3 O4 -pDNA-(ss)373 LPNPs were 302.33 nm in size. In addition, their zeta potential was 4.66 mV, and they had good biocompatibility. The optimal nanoparticles/pDNA ratio was 5 : 1, as shown by gel retardation assay. In this characterization, compared with other LPNPs, the modified single Ang or without the addition of the Fe3 O4 MNPs, the penetration efficiency of the BBB model formed by hCMEC/D3 cells, and the transfection efficiency of C6 cells using pEGFP-C1 as the reporter gene were significantly improved with Ang-TAT-Fe3 O4 -pDNA-(ss)373 LPNPs in the magnetic field.